Tanggung Jawab TNCs Terhadap Pelanggaran Hak Asasi Manusia Dan Lingkungan Dalam Perspektif Hukum Internasional Dan Hukum Hak Asasi Manusia Internasional - Sri Wartini (Fakultas Hukum Universitas Islam Indonesia, 2006)
International Human Rights Law and International Environmental Law is not able to protect efectively the violation of human rights and the righ to fenviromental protection exercised by TNCs, because TNCs is not subject of international law. The establishing and exercising soft-law such as code of conduct, global compactand OECD guide lines is expected to change the attude of TNCs In the future.